PENERAPAN MEDIA LAYANG-LAYANG UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS III MATERI ENERGI ALTERNATIF DI SDN KALICARI 01 KOTA SEMARANG - Mina Fujika Indriyani; Joko Sulianto; Ikha Listyarini; Suharno (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The purpose of this research is to improve the learning outcomes of Indonesian students by using the application of kite media in the learning process on class III alternative energy sources at SDN Kalicari 01 Semarang. This type of research is action research. The research subjects totaled 28 students. The data that has been collected is raw data then processed, processing summary data from raw data using certain methods or formulas. Summary data obtained from data processing can be in the form of totals, averages, percentages, and so on. The results of the initial test before being given the action using kite media obtained an average value of 61.8 with a classical completeness percentage value of 43% or as many as 12 students who completed KKM while 16 other students had not / did not complete. And the learning outcomes of students after being given action using kite media have increased from before the action. In action I, an average value of 69.7 was obtained with a classical completeness percentage of 54% or as many as 15 students who had completed their studies. students who have finished studying. In action III, an average value of 87.5 was obtained with a classical completeness percentage of 93% or as many as 26 students who had completed their studies. Based on the results of data analysis, it can be concluded that using kites as media can improve the learning outcomes of grade 3 students at SDN Kalicari 01 Semarang.